Water splitting for hydrogen production with ferrites - Han, Sang Bum; Kang, Tae Bum; Joo, Oh Shim; Jung, Kwang Deog (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The water splitting reaction by a thermo-chemical cycle using ferrites was investigated for H-2 production. In the first step (activation step), ferrites were thermally reduced at 1200 degrees C to form an oxygen-deficient ferrite. In the second step (water splitting step), the activated ferrites were oxidized by water at 800 degrees C to produce hydrogen. Among the prepared ferrites, Ni-ferrite was found to be the most suitable for H-2 production. NiFe2O4 produced an average of 0.442 cm(3)/g Cycle of H-2. The H2 productivity of the Ni-ferrite was much higher than that of the other ferrites at the same temperature. XRD showed that the crystal structure of NiFe2O4 during the redox reaction was not changed during the repeated cycles, indicating that NiFe2O4 was an excellent material in terms of structural stability and durability. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CARBON-DIOXIDE; SOLAR HYDROGEN; DECOMPOSITION; 2-STEP; OXYGEN; H2O; REACTIVITY; SYSTEM; H-2